Heavy Metals in Water German-Polish Szczecin (Oder-) Lagoon and Their Potentiality in Health Risk Assessment - Daniszewski, Piotr (Asian Journal of Chemistry, 2014)
Present research work deals with the quantification of toxic heavy metals in the water samples collected from in the lakes of German-Polish Szczecin (Oder-) Lagoon. It was observed that the concentration of cadmium was 0.86-0.47 ppm, chromium ranged 0.93-0.61 ppm, copper ranged 0.09-0.04 ppm, mercury ranged 0.09-0.04 ppm, nickel ranged 2.97-2.43 ppm, lead ranged 0.09-0.04 ppm, zinc ranged 4.12-2.84 ppm.